2006
DOI: 10.1101/gad.396106
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant mH2A1.1 interferes with transcription by down-regulating PARP-1 enzymatic activity

Abstract: The histone variant mH2A is believed to be involved in transcriptional repression, but how it exerts its function remains elusive. By using chromatin immunoprecipitation and tandem affinity immunopurification of the mH2A1.1 nucleosome complex, we identified numerous genes with promoters containing mH2A1.1 nucleosomes. In particular, the promoters of the inducible Hsp70.1 and Hsp70.2 genes, but not that of the constitutively expressed Hsp70.8, were highly enriched in mH2A1.1. PARP-1 was identified as a part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 42 publications
11
156
0
3
Order By: Relevance
“…In this model, PARP-1 might function to compact chromatin in regions of the genome packaged with macroH2A-containing nucleosomes, contributing to heterochromatin formation and transcriptional repression. While this work was under review, Ouararhni et al (32) reported that macroH2A1.1 associates with and inhibits PARP-1 and that transcriptional repression of a heat shock gene is mediated by macroH2A1.1 and PARP-1, consistent with a role for the macroH2A-PARP-1 interaction in transcriptional silencing. (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In this model, PARP-1 might function to compact chromatin in regions of the genome packaged with macroH2A-containing nucleosomes, contributing to heterochromatin formation and transcriptional repression. While this work was under review, Ouararhni et al (32) reported that macroH2A1.1 associates with and inhibits PARP-1 and that transcriptional repression of a heat shock gene is mediated by macroH2A1.1 and PARP-1, consistent with a role for the macroH2A-PARP-1 interaction in transcriptional silencing. (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Cell extracts from the tagged cells were prepared and the e-H3.1 and e-CENP-A prenucleosomal complexes were purified by sequential immunoprecipitations with antiFLAG antibody followed by antiHA antibody (29). The proteins associated with e-CENP-A and e-H3.1 were separated in 4-12% gradient PAGE containing SDS and silver stained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prenucleosomal CENP-A and H3.1 complexes were purified from soluble nuclear extracts prepared from stable HeLa cell lines expressing either CENP-A or H3.1 proteins fused to C-terminal FLAG and HA epitope tags (e-CENP-A/e-H3.1). A tandem affinity purification protocol on antiFlag antibody-conjugated agarose followed by antiHA purification and peptide elution was used (29).…”
Section: Methodsmentioning
confidence: 99%
“…Generation of HeLa cell lines expressing the N-terminal FLAG-HA epitope-tagged (E)-TRIM24 protein was performed by retroviral infection, extract preparation and tandem affinity purification using the FLAG and HA tags were all performed essentially as previously described (34). Purified complexes were analyzed on 4-12% Tris-Bis NuPage gels (Invitrogen) and stained with Coomassie blue.…”
Section: Methodsmentioning
confidence: 99%